2019
DOI: 10.14198/jhse.2019.143.08
|View full text |Cite
|
Sign up to set email alerts
|

Soccer in the mass media: Examining the role of metaperceptions of goal orientation on spectators’ moral functioning

Abstract: Watching soccer can be a source of leisure and enjoyment. However, the behaviour of some spectators is a concern that might be related to competitive sport and its handling by the mass media. This study analysed the relationship between the exposure to soccer in the media and the spectators' moral functioning. Participants were college students (N = 355), who completed questionnaires assessing the time spent watching/listening/reading soccer programming, metaperception of goal orientations, and moral functioni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 32 publications
(46 reference statements)
2
6
0
1
Order By: Relevance
“…In effect, there are statistically significant differences in the negative comments made, according to the geographical area variable, with a 53% increase in games and matches in rural areas. In this sense, it coincides with previous authors [20], who have concluded that the sociocultural context is an important variable between the behavior of spectators at sporting events and how sporting success is interpreted. The reason is due to the urban areas are characterized by having a higher population density and human diversity.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…In effect, there are statistically significant differences in the negative comments made, according to the geographical area variable, with a 53% increase in games and matches in rural areas. In this sense, it coincides with previous authors [20], who have concluded that the sociocultural context is an important variable between the behavior of spectators at sporting events and how sporting success is interpreted. The reason is due to the urban areas are characterized by having a higher population density and human diversity.…”
Section: Discussionsupporting
confidence: 91%
“…Conversely, in rural areas availability, people manage to create and develop a sense of belonging to the territory. Moreover, results have shown that, according to previous studies [20], some clear connections between the comments made by family spectators and the sport atmosphere.…”
Section: Discussionsupporting
confidence: 53%
See 3 more Smart Citations